Nipple‐sparing mastectomy as treatment for patients with ductal carcinoma in situ: A 10‐year follow‐up study. Issue 3 (15th November 2017) - Lago, Víctor; Maisto, Vincenzo; Gimenez‐Climent, Julia; Vila, Jose; Vazquez, Carlos; Estevan, Rafael
Abstract: The objective was to determine the 10‐year oncological safety of nipple‐sparing mastectomy (NSM) in patients diagnosed with ductal carcinoma in situ (DCIS). The use of NSM preserves the nipple‐areola complex (NAC). As residual fibroglandular breast tissue can remain behind the spared NAC, its use for patient with breast cancer is controversial. The oncologic outcomes and complication rates after performing NSM compared to other techniques are still under debate and a concern when treating patients with breast cancer. We retrospectively reviewed 69 consecutive NSM patients diagnosed with DCIS during 1984‐2016 at the Valencia Institute of Oncology, Valencia, Spain. 13 of 82 reviewed cases were excluded from the analysis owing to the presence of invasive tumor in the final pathologic report. All 69 patients who underwent NSM due to DCIS were included and analyzed. The indications were as follows: unfavorable correlation between tumor size and breast size in 53 patients, 10 patients with multifocal or multicentric tumors and breast cancer recurrence after breast‐conserving surgery in six patients. The reconstruction was performed using a prosthetic implant: saline‐filled implant 33 (47.8%) or tissue expander 36 (52.2%). No frozen section was performed in the patients included in our study. The presence of DCIS was confirmed in 60 patients and in the other nine patients we found no tumor in the mastectomy specimen (removed due to excisional biopsy procedure). High risk features were: tumor grade 3 in 27 (39.2%) cases and comedonecrosis in 32 (46.4%) cases. In 27 patients surgical axillary staging was performed and no residual disease in the axilla was observed. After a mean follow‐up period of 142.6 ± 70.7 months no nipple necrosis was observed. In 15 patients (21.7%) an additional surgical procedure was performed. 48 patients (69.6%) did not receive any adjuvant treatment. Adjuvant hormone therapy was given to 20 patients (29%) and one patients received radiation therapy (1.4%). Eight patients showed a local relapse (11.6%). One patient developed a recurrence within the nipple‐areola region presented as Paget's disease (1.4%). One patient presented a thorax wall relapse after 42 months of disease‐free survival and died because of metastatic dissemination of the tumor. The DFS rate was 88.4% and the overall survival rate was 98.6%. In patients with DCIS that are not candidates to breast‐conserving therapy, NSM is a realistic option of treatment. No case of nipple necrosis was observed. A low rate of nipple relapse (1.4%) and a good survival rate (98.5%) were observed after a median follow‐up of 142.6 months.